Continuous Knowledge Transfer – A pragmatic approach to knowledge sharing in the European Patent Office. (December 2016) - Schombacher, Hanno; Lahorte, Philippe; Vistisen, Lars; Versluis, Anton; Martins, Fernando Correia; Meyer, Wolfram; Patras, Paula; Bardella, Xavier; Roux, Florence; Kreuter, Angela; Scott, Jeremy
Abstract: During the last 15 years the European Patent Office (EPO) has established an internal peer to peer knowledge sharing process. This process is driven by a team of knowledge sharing experts, collated in a team called CKT – Continuous Knowledge Transfer. The process works in a complementary manner to classical and well-elaborated learning and development activities of the international organisation. The article aims at describing the motivation for creating such process, the development of CKT and its structure and tools. The basic components of the process are presented and success factors elaborated.